2016
DOI: 10.1111/jdi.12471
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ipragliflozin in Japanese patients with type 2 diabetes stratified by body mass index: A subgroup analysis of five randomized clinical trials

Abstract: Aims/IntroductionThe influence of overweight/obesity on the clinical efficacy and safety of sodium‐glucose co‐transporter 2 inhibitors is unclear. We carried out a pooled analysis to examine the impact of body mass index on the efficacy and safety of ipragliflozin.Materials and MethodsPatient‐level data were pooled for five Japanese double‐blind trials (NCT00621868, NCT01057628, NCT01135433, NCT01225081 and NCT01242215) in which patients were randomized to ipragliflozin or a placebo as monotherapy, or in combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
33
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 22 publications
12
33
2
Order By: Relevance
“…The following indicates the strengths of this study. First, we showed that ipragliflozin ameliorated the index of hepatic steatosis in humans, although it has been reported that ipragliflozin improves the serum alanine aminotransferase levels in patients with type 2 diabetes [10][11][12]. Second, we investigated whether improvement of obesity or glucose intolerance could influence the FLI changes observed with ipragliflozin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The following indicates the strengths of this study. First, we showed that ipragliflozin ameliorated the index of hepatic steatosis in humans, although it has been reported that ipragliflozin improves the serum alanine aminotransferase levels in patients with type 2 diabetes [10][11][12]. Second, we investigated whether improvement of obesity or glucose intolerance could influence the FLI changes observed with ipragliflozin treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Genital infections were confirmed to have a higher incidence in an empagliflozin‐treated group (men 5.0%, women 10.0%) compared with a placebo group (men 1.5%, women 2.6%), respectively, and a canagliflozin‐treated group (men 3.8%, women 10.7%) compared with a placebo group. Pooled analysis of the incidence of genital infection in Japanese female patients showed a higher incidence in an ipragliflozin‐treated group (5.3%) compared with a placebo group (1.9%). It is generally accepted that genital infections are seen at higher frequencies in female than male diabetes patients (Table ).…”
Section: Major Adverse Events: Hypoglycemia Skin Disorders and Genimentioning
confidence: 97%
“…Ipragliflozin is the first SGLT2 inhibitor to be approved for the treatment of patients with type 2 diabetes mellitus in Japan, as monotherapy or in combination with other OAM. Previous randomized placebo‐controlled studies have shown that administration of ipragliflozin to patients with type 2 diabetes mellitus improved glycemic control and had low rates of adverse events. Although treatment with SGLT2 inhibitors has been recommended for patients with type 2 diabetes mellitus who are relatively young and obese in daily clinical practice in Japan, the efficacy and safety of ipragliflozin for elderly or non‐obese patients are less clear, and there is a need to evaluate the drug based on patient background in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%